A new species of Nanhaipotamon Bott, 1968 (Crustacea: Decapoda: Brachyura: Potamidae) from Zhuhai, Guangdong Province, China - Huang, Chao; Huang, Jian Rong; Ng, Peter K. L. (Zootaxa, 2012)
A new species of freshwater crab of the genus Nanhaipotamon Bott, 1968, N. zhuhaiense n. sp. is described from Zhuhai,Guangdong Province, southern China. The new species inhabits mud burrows on the banks of densely vegetated creeksand is sympatric with N. guangdongense Dai, 1997. Its distinctive bluish-white coloration in life as well as the characteristic morphology of the male first pleopod easily distinguishes the species from congeners.